Retention over Attraction: A Review of Women’s Experiences in the Australian Construction Industry; Challenges and Solutions - Amir Naser Ghanbaripour; Roksana Jahan Tumpa; Riza Yosia Sunindijo; Weiwei Zhang; Parinaz Yousefian; Ranka Novak Camozzi; Carol Hon; Nima Talebian; Tingting Liu; Mina Hemmati (Buildings, 2023)
Despite substantial investments and efforts by governments, construction organisations, and researchers, the construction industry remains one of the most male-dominated industries in Australia, with women being underrepresented numerically and hierarchically. Efforts to attract and retain women in construction have been implemented inconsistently on an ad hoc basis. As part of a larger research project that focuses on retaining women in the Australian construction industry, this research conducts a systematic literature review (SLR) in accordance with the PRISMA guidelines. The objective is to explore the factors that influence women’s careers and their experiences in the Australian construction industry that have been identified in the literature over the past three decades. Additionally, the findings are anticipated to inform future efforts to evaluate the effectiveness of current initiatives to retain women and develop a framework for enhancing women’s experiences and retaining them in this profession. This SLR revealed that excessive and rigid work hours, gendered culture and informal rules, limited career development opportunities, and negative perceptions of women’s abilities are the main factors and issues that cause women to leave the industry. Among these, rigid and long work hours seem to be the foremost factor to be prioritised. Understanding the roles of key variables in driving this cultural change is important to ensure that concrete progress is made. The paper draws three major aspects from the literature in which solutions and policies can be researched, designed and implemented.